2019
DOI: 10.3390/su11102818
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Agricultural Land Use Pattern Dynamics on Elephant Habitat Depletion and Human-Elephant Conflict in Sri Lanka

Abstract: The drastic depletion of elephant habitats in the dry zone of Sri Lanka has led to intense human-elephant conflict (HEC) in a region that is home to one of the celebrated agrarian settlements in Asia. Known as the tank villages, these settlements have a long history of human coexistence with elephants and other wild animals. However, the escalating incidence of human-elephant fatalities and crop losses to farmers indicates that the mode of interaction between the tank village inhabitants and the elephants has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Mortality from intentionally caused deaths was more common than unintentional causes. It is illegal to kill an elephant in Sri Lanka, but when pressed, people have strong motivation to protect themselves and their property (Anuradha et al 2019). Equally as important to preserving elephants is ensuring the well-being of the people that live around them, as coexistence is largely dependent upon tolerance by local communities (Barua et al 2013, Kansky et al 2016, Saif et al 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality from intentionally caused deaths was more common than unintentional causes. It is illegal to kill an elephant in Sri Lanka, but when pressed, people have strong motivation to protect themselves and their property (Anuradha et al 2019). Equally as important to preserving elephants is ensuring the well-being of the people that live around them, as coexistence is largely dependent upon tolerance by local communities (Barua et al 2013, Kansky et al 2016, Saif et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Human-elephant conflict (HEC), most often through crop-raiding, is a major impediment to the wellbeing of humans and elephants in elephant range countries. Asian elephants are threatened primarily by habitat loss and fragmentation, exacerbating HEC in areas with growing human populations (Choudhury et al 2008, Barua et al 2013, Wilson et al 2015, Anuradha et al 2019, Menon and Tiwari 2019. At the same time that HEC threatens the safety and livelihood of local human communities, elephants are also critically important to the normal functioning of the ecosystems where they live (Blake and Hedges 2004, Campos-Arceiz and Blake 2011, Tscharntke et al 2012.…”
mentioning
confidence: 99%
“…During the past two decades, the integrity and functions of VTCSs have been degraded significantly affecting the provision of ecosystem goods and services. For example, deterioration of micro-land use components and upstream catchment forest has had a significant impact on biotic diversity (species diversity, functional diversity and vegetation structure), abiotic heterogeneity (soil erosion and land degradation) and imbalance of water budget (soil moisture, evaporation, surface runoff), leading to a significant reduction in the capacity of supplying and regulating ES in the VTCS [87][88][89][90]. Thus, the study examined the identified causal factors and their interactive relationships [27,28] within the framework of resilience, adaptive capacity, and the vulnerability (RACV) concept [29], while incorporating exposure and sensitivity indices specific to Mahakanumulla VTCS.…”
Section: Productivity Issues Linked With Socio-ecological Properties and Restoration Challengesmentioning
confidence: 99%
“…Recent studies have shown that various factors impact the ecological productivity of the VTCSs. For instance, agricultural expansion into ecologically sensitive areas of the major VTCS zones due to demographic changes and urbanization has led to a drastic reduction in forest cover during the last two decades [8,89,90]. The degradation of the integrity and functionality of the cascade ecology has resulted in the reduction of capacity to supply ES and increased severity of droughts [6].…”
Section: Productivity Issues Linked With Socio-ecological Properties and Restoration Challengesmentioning
confidence: 99%
See 1 more Smart Citation